The Implementation of Age Replacement Method for VH-Drum Components for Baby Diaper Production Machines at PT. XYZ: The Implementasi Metode Age Replacement Komponen VH-Drum Mesin Produksi Popok Bayi Pada PT. XYZ - Fauzi, Fu'ad; Jakaria, Ribangun Bamban (Universitas Muhammadiyah Sidoarjo, 2021)
At PT. XYZ often experiences damage problems during the production process, the high level of damage often causes corrective activities. The high level of corrective activities is caused by replacing components after the component is damaged and this causes high downtime. The average damage to the vh-drum component has a damage frequency of 23 times and a downtime of 3052 minutes in a year. In this study, the aim was to obtain a time interval for replacing sonic seals to reduce maintenance costs by using the age replacement method. Based on the results of the analysis and discussion that has been carried out, it can be concluded that the replacement interval for the Vh-Drum Component of the Baby Diaper Production Machine has decreased with the previous down time of 3052 with the replacement interval for the Vh-Drum Component of the Baby Diaper Production Machine is Baby Diaper is 70,301 days with a total costs IDR 21,735,945, 67 days with a total cost of IDR 22,831,972, 60,883 days with a total cost of IDR 25,018,276. Meanwhile, the smallest cost falls at an interval of 70,301 days with a total cost of Rp. 21,735,945.